PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN (Studi pada Pelanggan Alicia Skin Care Purwodadi) - Diana Ari Cahyani, 12.05.51.0172; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2017)
The purpose of this study was to analyze the influence of the quality of service, product and price perception of the satisfaction and impact on customer loyalty Alicia Skin Care Purwodadi.The population in this study is the customer in Alicia Skin Care Purwodadi that uses member Alicia Skin Care. The sample in this study as many as 100 people. The sampling technique used purposive sampling. The criteria for the sample in this study is the customer must be at least 17 years of age and a minimum treatment 5 times in the last 3 months. The analysis tool used is multiple linear regression.The results of the analysis can be concluded that: Quality of service positively affects customer satisfaction. Product quality positively affects customer satisfaction. Perception prices positively affects customer satisfaction. Quality of service is a positive effect on customer loyalty. Product quality positively affects customer loyalty. Perception prices positive effect on customer loyalty. Customer satisfaction has positive effect on customer loyalty. Customer satisfaction does not mediate the effect of service quality on customer loyalty. Customer satisfaction does not mediate the effect of product quality to customer loyalty. Customer satisfaction does not mediate the effect of price perception on customer loyalty. Keywords: quality of service, product quality, perceived price, customer satisfaction and loyaltyDAFTAR PUSTAKA Aaker, David A. and Kevin L. Keller. 1990. Consumer Evaluations of BrandExtensions. Journal of Marketing. 1(54): 27-41Alma, Buchari. 2003. Manajemen Pemasaran dan Pemasaran Jasa. Edisi Revisi. CV Alfabeta. BandungBei, Lien-Ti; Chiao Yu-Ching. 2001. “An Integrated Model For The Effect OfPerceived Product, Perceived Service Quality And Perceived PriceFairness On Consumers,” Kumpulan Jurnal Terjemahan BidangPemasaran I, Magister Manajemen, Universitas Diponegoro.Dewi Kurniawati, Suharyono, dan Andriani Kusumawati. 2014. Pengaruh Citra Merek Dan Kualitas Produk TerhadapKepuasan Dan Loyalitas Pelanggan (Studi pada Pelanggan KFC Cabang Kawi Malang). Jurnal Administrasi Bisnis (JAB). Vol. 14 No. 2 September 2014Djarwanto PS dan Pangestu Subagyo. 2002. Statistik Induktif. Edisi 4. : BPFEYogyakartaFeigenbaum, A.V. 2000. Kendali Mutu Terpadu. Jilid 1. Edisi Ketiga. Erlangga. Jakarta.Ghozali, Imam. 2011. Aplikasi Analisis Multivariate Dengan Program IBM SPSS 19.Badan Penerbit Universitas Diponegoro, Semarang.Goetsch, David L., Stanley B. Davis. 2000.The Total Quality Approach to Quality Management. 3rded.. New Jersey: Prentice HallGriffin , Jill. 2005. Customer Loyalty, Menumbuhkan dan Mempertahankan Kesetiaan Pelanggan. Penerbit : Erlangga, JakartaHaryanto, Resty Avita. 2013. Strategi Promosi, Kualitas Produk, KualitasLayanan Terhadap Kepuasan Pelanggan Pada Restoran Mc donald’sManado. Jurnal. Manado : Fakultas Ekonomi dan Bisnis, Universitas SamRatulagiHilyatul Azizah. 2013. Pengaruh Kualitas Layanan, Citra dan KepuasanTerhadap Loyalitas Nasabah. Management Analysis Journal. UniversitasNegeri SemarangHurriyati, Ratih. 2005. Bauran Pemasaran dan Loyalitas Konsumen; Bandung: ALFABETAIndriantoro, Nur., Bambang Supomo. 2009. Metodologi Penelitian Bisnis untuk Akuntansi dan Manajemen. Edisi Pertama. Yogyakarta : BPFE Yogyakarta.Jiang, Pingjun & Rosenbloom, Bert 2005. CustomerIntention to Return Online: Price Perception,Attribute-level Performance, and SatisfactionUnfolding Over Time. European Journal of Marketing. Vol. 39. pp. 150-175Kotler, Philip. 2000.Manajemen Pemasaran. Edisi Milenium. Jakarta. PrehallindoKotler, Philip dan Gary Armstrong. 2001.Prinsip-prinsip Pemasaran. Jilid 1. Edisi Kedelapan. Jakarta. Erlangga.Kotler, Philip. 2004. Manajemen Pemasaran: Analisis, Perencanaan, implementasidan Kontrol, Edisi Sebelas. Alih Bahasa, Hendra Teguh. Jakarta: Penerbit PT.PrenhallindoKotler, Philip; Armstrong, Garry. 2008. Prinsip-prinsip Pemasaran. Jilid 1. Erlangga. JakartaKotler dan Keller. 2009. Manajemen Pemasaran. Jilid I. Edisi ke 13. Jakarta:ErlanggaLeliana, Suryandari. 2004. Persepsi Harga Jual dalam Perilaku Belanja Konsumen. Jurnal Bisnis dan ManajemenMardalis, Ahmad. 2005. Meraih Loyalitas Pelanggan. Jakarta : Balai PustakaMehdi, J. S., Mojgan, K., and Masoud, J. 2013.“Investigation of the Effective Factors onBrand Loyalty and Repurchase Intention (Case study: Iranian Consumers)”. Research Journal of Recent Sciences. Vol. 2, No. 2:10-17Mowen, J.C, Minor.M. 1998. Consumer Behavior. New York : Prentice Hall IncNalau, Antonio, Syarifah Hudayah, dan Muhammad Wasil. 2012. Brand Image Terhadap Loyalitas Pelanggan J.Co Donuts dan Coffee di Plaza Mulia Samarinda. Jurnal Ekonomi. Universitas MulawarmanOliver, Riscrd L, 1997. Satisfaction A Behavioral Perspective On The Consumer.McGraw-Hill Education, SingaporeParasuraman, V., A. Zeithaml and L. L. Beny. 1988. Servqual A. Multiple item forMeasuring Customer Perception of ServiceQuality. Journal of Retailing. 64. pp.12-40Peter, J Paul dan Olson, Jerry C. 1996. Customer Behaviour and Marketing Strategy. 4th Edition. New York : McGraw Hill CoSelnes, Fred. 1993.. An Examination of the Effect of Product Performanceon Brand Reputation. Satisfaction and Loyalty.European Journal ofMarketing. Vol.27. No 9Schnaars, Steven P. 1991. Marketing Strategy : A customer DrivenApproach.2nd ed. New York: The Free PressSuki, Norazah Mohd. 2013. Students’ Demand for Smartphones: StructuralRelationships of Product Features. Brand Name. Product Price andSocial Influence. Campus-Wide Information Systems. Vol. 30 No. 4. 2013.Sunyoto, Danang. 2015. Manajemen Bisnis Ritel. Yogyakarta: CAPSSuryani, Tatik. 2008. Perilaku Konsumen: Implikasi Pada Strategi Pemasaran. Yogyakarta: Graha IlmuSyahputa, M.2010. Pengaruh Kepuasan Merekdan Kepercayaan Merek terhadap LoyalitasMerek Handphone Samsung di kota BandaAceh”. Skripsi. Universitas Syiah KualaTimm, Paul R. 2005.50 Ideas To Keep Your Customer. PT. Buana IlmuPopuler. JakartaTjiptono, Fandi dan Gregorius Candra. 2005. Service, Quality, and Satisfaction.Yogyakarta: AndiTjiptono, Fandy. 2008.Strategi Bisnis Pemasaran. Andi. YogyakartaTjiptono, Fandy. 2011, Pemasaran Jasa, Bayumedia, MalangXian, Guo li et al. 2011. Corporate, Product, andUser Image Dimensions and PurchasIntentions.Journal of Computers. 6(9):1875-1876Taylor, (1998), Bennett and Rundle (2004), dan Schultz, (2005)Darnesta (1999)Kapferer (2008),Kotler (2002)Kotler dan Amstrong, (2011)Tjiptono (2002)Tjiptono (2001)Aaker (1991)Tatiana Anatolevena Anisimova (2007),Sunyoto (2015